Análise de práticas do pré-desenvolvimento de novos produtos: estudo de múltiplos casos - Costa, Marcela Avelina Bataghin (2014)
Pre- development phase and corresponds to the activities ranging from identifying opportunities to generate product concepts. Throughout these activities there is a dynamic and complex flow of information about business strategies, requirements and market trends, technological alternatives and resource allocation. At this stage important decisions are made, and if misleading may result in failures in the performance of the new product. The subject has gained importance in recent years, however, there is still not an understanding on how to coordinate the activities of the predevelopment or which results are expected in this phase, therefore being a gap in the literature. This thesis aims to identify and analyze the practices, technical and tools what are adopted in front-end development in a sample of manufacturing firms. Through systematic literature review identified ten reference models for the front end development. These were published between 1988 and 2013 and seek to systematize the activities of pre-development and guide managers in conducting phase, proposing technical and management support tools. 57 different techniques have been identified. Through multiple case studies it was observed that all studied companies adopt referential models for conducting the activities of front end development. As in literature these models followed by companies differ mainly in relation to the number of stages or activities, but adopt some techniques and tools as well diffused in the literature. We observe that the most common practices in all companies can be grouped into early, middle and end activities, which divide the front end development in three distinct phases. For every moment of the predevelopment can be selected a set of techniques and support tools. These techniques and tools do not necessarily have to be adopted together because they have different natures, but are a "package" of suggestions to be considered. In addition, internal and external factors in the companies affect such practices. It was also possible to identify, in the companies analyzed, finding it difficult to measure the performance of the activities of the pre-development phase itself, and the PDP as a whole, so some possible performance indicators for this phase were suggested. Another difficulty associated with the use of these techniques and tools is that they require financial and time resources, and all require the skills of those who lead. Therefore, the most modern and best potential for achieving results technique can be ineffective if conducted by people who do not have necessary skills and appropriate technical support.